Risks in the supply chain: strategies to mitigate disruptions in the production and distribution of perishable foods- a case study - Buenaño, Edinson (2024)
The present study aims to conduct an analysis in the food sector, with a case study in Salinas Canton, Santa Elena Province, where strategies will be implemented to mitigate risks in the supply chain and logistics, thereby promoting greater market sustainability. Employing a mixed methodological approach, it combines bibliographical research with reviewed scientific bases to develop these strategies. Additionally, a survey will be conducted as a technique to understand customer preferences and tastes, with the goal of introducing a new product that meets consumer needs. A meticulous standardized production and distribution scheme will be established to minimize lead times and waste. The data obtained demonstrates reliability with a value of 0.848 and positive correlations between variables. Sales projections will be established to assess market influence on the new product, and costs will be determined through financial studies. Time studies, critical path analysis, and operations diagram will be conducted to optimize available resources and maximize project profitability. Analyzing minimum process times aims to reduce errors by 15% while maintaining market product loyalty and credibility.